ANALYSIS OF STUDENT’S ABILITY IN IDENTIFYING FIGURATIVE LANGUAGE IN MARIAH CAREY’S SONGS - Viona BR Sembiring (BASIS (Bahasa dan Sastra Inggris), 2020)
Figurative language is one way of conveying words other than the normal way. This helps song writers compose and produce beautiful songs. Figurative language is part of semantics. Semantic is the study of meaning that is used to understand human expression through language. With semantic we can know the true or actual meaning in a song. This study aims to find student’s ability in identifying kinds of figurative language and their meanings in lyrics of Mariah carey selected song. Descriptive qualitative method is the method used in this study. The instrument for collecting the data was test questions which consisted of 12 questions. In this research, the subject was 11th grade class of SMA Swasta GKPI Padang Bulan which consisted of 28 students. The result of data analysis shows that the students mean score is 76,7 the highest score is 92, while the lowest score is 50. There were 4 student, (14,3%), belonged to the very good level and 21 students (75 %), belonged to the good level and there were 3 students, (10,7%), belonged to sufficient level.Kind of figurative language was found in Mariah Carey songs lyric are simile, metaphor, hyperbole, and personification. The dominant types of figurative language found in Mariah Carey song lyrics is metaphor.From an analysis ,the researcher concluded that most of the students of the second grade class of SMA Swasta GKPI Padang Bulan Medan got dificulties to different between metaphors and personifications in identifying figurative language in mariah carey’s songs lyrics.